STRATEGI MENGHADAPI PEMERIKSAAN PAJAK: UPAYA LEGAL DALAM KERANGKA SISTEM ADMINISTRASI PERPAJAKAN - Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Self assessment system stipulated by tax policy has given taxpayers full trust in presenting data to perform their tax obligations. This means that as long as tax officers agree and accept taxpayer’s report, this can be assumed that the reportprovided is true. In order to examine tax compliance level, tax officer(s) will do tax audit. The scope of tax audit includes providing the audit strategic planning; reviewing the tax implementation; and providing recommendations from tax evaluation. The compliance to the provision of tax regulations represents the effort from taxpayer(s) and tax officer(s) in tax administrationframework.